A Positive Affective Neuroendocrinology Approach to Reward and Behavioral Dysregulation - Welker, Keith M.; Gruber, June; Mehta, Pranjal H. (Frontiers in Psychiatry, 2015)
Emerging lines of research suggest that both testosterone and maladaptive reward processing can modulate behavioral dysregulation. Yet to date, no integrative account has been provided that systematically explains neuroendocrine function, dysregulation of reward, and behavioral dysregulation in a unified perspective. This is particularly important given specific neuroendocrine systems are potential mechanisms underlying and giving rise to reward-relevant behaviors. In this review, we propose a forward thinking approach to study the mechanisms of reward and behavioral dysregulation from a positive affective neuroendocrinology (PANE) perspective. This approach holds that testosterone increases reward processing, which increases the likelihood of behavioral dysregulation. Additionally, the PANE framework holds that reward processing mediates the effects of testosterone on behavioral dysregulation. We also explore sources of potential sex differences and the roles of age, cortisol, and individual differences within the PANE framework. Finally, we discuss future prospects for research questions and methodology in the emerging field of affective neuroendocrinology.